STUDY OF INFORMATION SECURITY OF THE INFORMATION SERVICES MARKET - Natalia Kondratenko (Izdevnieciba "Baltija Publishing", 2021)
The article is devoted to the study of information security of the information services market. The subject of the research is information security, and the goal of the paper is to study the information security of the information services market. Information security is considered a socio-economic challenge that can be addressed through the confident actions of the state. Data analysis confirmed the problem of information security at different levels. Information security is aimed at protecting information from unauthorized access. The development and transformation of the information services market depend on the quality metrics of the Internet. This paper deals with the issue of maintaining a sufficient level of information transparency, which is related to and interdependent on information security. The main risks and threats caused by the active introduction of information technologies and the advancement of the information services market are specified. The study found that in the day-to-day operations of each company, many risks can affect the information system due to information security breaches. Social engineering involves the use of psychological techniques to mislead users by providing information or access for attackers. In order for the company to cope with external risks in the information services market, it is necessary to build a strong risk management information system. The process of risk management is ongoing and iterative in nature, it must be repeated indefinitely as new threats and vulnerabilities emerge, especially external ones. The choice of countermeasures or controls used must strike a balance between productivity, cost, effectiveness, and the information value of the asset being protected. Conclusions: the research identified the basic principles of information security, namely confidentiality, integrity, and availability. Moreover, to increase the information security of the companies which are participants in the information services market, the author proposes implementing a range of measures within the company. Information security in the information services market is a marker of the crucial difference between the information society and the industrial society. The main hallmark of the information society is its openness. This means a significant reduction and thus a general lack of confidential information for society. The study established that the digitalization of the economy is modifying the information services market. The research findings may prove useful to businesses and governments to boost information security of the information services market. The research is based on the methods of theoretical generalization and comparison to define the concept of "information security" and its interrelations with other definitions of the relevant terminological framework. Analysis, synthesis, and scientific abstraction were used to identify factors affecting the risks and threats to information security of the information services market. There were used methods of analysis, comparison and generalization when summarizing research findings.